Robust Optimization of Linear Precoders/Decoders for Multiuser MIMO Downlink with Imperfect CSI at Base Station - Hao Li; Changqing Xu (2007 IEEE Wireless Communications and Networking Conference, 2007)
A robust scheme is proposed to optimize the linear precoders/decoders for MIMO downlinks where the available channel state information (CSI) at base station (BS) is imperfect. The objective is to minimize the sum mean square error (SMSE) over all data sub-streams under a per-user transmit power constraint. By using an iterative procedure, the proposed scheme extends the existing optimization algorithm for the single-user MIMO system with perfect CSI to solve approximately the minimizing SMSE problem in the multiuser MIMO downlink with imperfect CSI at BS. Simulation results demonstrate that the proposed scheme can effectively mitigate the performance loss induced by the imperfect CSI and can provide largest possible diversity as well as increased throughput.